Peran Etika Komunikasi Publik Dalam Mencegah Pernyataan Kontroversial Pejabat Publik - Zulafa, Izzuddin Rahmat; Putro, Adi Nugroho Susanto; Asih, Situ (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2026)
This study aims to analyze the role of public communication ethics in preventing controversial statements (blunder statements) made by public officials. The research is motivated by the increasing number of officials’ statements that trigger public controversy and reduce public trust. This study applies communication ethics theory using a qualitative phenomenological approach. The research subjects are public officials in Wonogiri Regency, selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and analyzed using Interpretative Phenomenological Analysis (IPA). The findings reveal that communication ethics is understood as a reflective practice involving data verification, consideration of social impact, and the use of clear and empathetic language. Blunders are not solely caused by message errors but also by differences in interpretation between communicators and audiences. Additionally, the speed and accuracy of responses in providing clarification play a crucial role in managing communication crises. Therefore, communication ethics functions as both a preventive and strategic mechanism to maintain public trust and social stability.